Highly crosslinked organosulfur copolymer nanosheets with abundant mesopores as cathode materials for efficient lithium-sulfur batteries. (10th February 2018) - Zeng, Shuaibo; Li, Ligui; Yu, Jingping; Wang, Nan; Chen, Shaowei
Abstract: Low sulfur utilization and poor cycling stability are two major factors that currently impede the wide-spread commercialization of lithium-sulfur (Li-S) batteries. Herein, sulfur-rich side chains are anchored onto Schiff-base copolymer of thiourea aldehyde resin (cp (S-TAR)) nanosheets via inverse vulcanization to form a large number of intermolecular crosslinkers as well as mesopores. Application of the resultant copolymer as a cathode material in Li-S batteries can not only provide abundant porous channels for Li + diffusion but also significantly alleviate the dissolution of polysulfides by chemical confinement through the covalent bonds between sulfur-rich side chains and TAR. With this novel polymer cathode, a Li-S battery prototype is constructed which can operate at 1 C for over 500 charge-discharge cycles at nearly 99% coulombic efficiency, showing an ultralow cyclic fading rate of 0.045% per cycle, and an outstanding high-rate response of up to 5 C. The present strategy demonstrates the great potential of using highly crosslinked organosulfur copolymers as high-performance polymer cathode materials for low-cost, high-energy density Li-S batteries. Graphical abstract: Highlights: Synthesis of highly crosslinked mesoporous organosulfur polymer nanosheets. The abundant mesopores enrich lithium ion diffusion channel. Remarkable rate performance and high cycling stability are achieved.